1985
DOI: 10.1039/f19858102845
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle neutron-scattering studies of silica sols in water at high temperatures

Abstract: The temperature dependence of the interparticle interactions in a silica sol have been investigated in the range 298-533 K by small-angle neutron scattering. By applying the rescaled mean spherical approximation (MSA), due to Hansen and Hayter, closed analytic solutions of the structure factor, S(Q), for a screened coulombic potential have been fitted to experimental scattering data to obtain the effective surface charge and potential of the silica particles. As the temperature is increased, marked reductions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…larger than 2 ram. However, using a 0.5 mm thick cell, we reproduced the earlier data (Shuin 1977;Matsuoka et al 1988;Ramsay and Booth 1983;Penfold and Ramsay 1985;Bunce et al 1985) almost completely. Artifacts are possible, but our observations appeared to be real.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…larger than 2 ram. However, using a 0.5 mm thick cell, we reproduced the earlier data (Shuin 1977;Matsuoka et al 1988;Ramsay and Booth 1983;Penfold and Ramsay 1985;Bunce et al 1985) almost completely. Artifacts are possible, but our observations appeared to be real.…”
Section: Introductionsupporting
confidence: 74%
“…glass capillary suggested an ordered structure from a peak in a SAXS curve for higher SiO2 and lower electrolyte concentrations (Matsuoka et al 1988). SANS studies on Ludox HS using a 1 or 2 mm quartz cell also indicated similar behaviors (Ramsay and Booth 1983;Penfold and Ramsay 1985;Bunce and Ramsay 1985). Table 2 summarizes the loci of peaks of the above scattering data.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations